Electrochemical synthesis of palladium nanoparticles in PVP solutions and their catalytic activity in Suzuki and Heck reactions in aqueous medium - Uberman, Paula Marina (2014)
Small palladium nanoparticles (PdNPs) with large-surface area were synthesized in aqueous media in the presence of poly(N-vinylpyrrolidone) (PVP) using a simple electrochemical method. Electroreduction of Pd(II) species on a vitreous carbon electrode was performed by application of a current density pulse and the resulting PVP–Pd dispersion was formed. Highly concentrated PdNPs suspensions, stabilized with PVP molecules were obtained in a short time at room temperature. The size and morphology of the nanostructures obtained depend on the current density (30 to 8 nm PdNPs, for current densities in the −100 and −350 mA cm−2 range). Nanoparticle structures with large-surface area were investigated by transmission electron microscopy. The surface area of the PdNPs notably increased when the current density is more negative. The resulting PVP-stabilized PdNPs showed a very high catalytic activity when they were used in Suzuki and Heck reactions. With elevated TON and TOF, and in aqueous medium, this catalytic system proved to be an environmental friendly alternative to the conventional Pd catalyst